Killers never sleep - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Buck Trammel western, 2024)
When gambler Adam Hagen takes wagers on the fate of notorious outlaw Ben Washington, who's in his custody, Sheriff Buck Trammel of Laramie and his deputy must place a high-stakes game of their own as a bunch of cutthroats team up to make some easy money.